Method for preparing cable sheath material from recycled plastic material and application of cable sheath material
By using the combination of plastic recycling materials and specific surfactants and tackifying resins, cable sheath materials with excellent shielding, anti-aging and mechanical properties are prepared, which solves the problem of easy aging of existing cable materials and realizes the feasibility of resource reuse and industrial production.
Patent Information
- Application Number
- CN202411801014.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-12-09
AI Technical Summary
Existing cable materials are prone to aging under the influence of wind, rain, sunlight, heat and ozone, resulting in deterioration of physical and mechanical properties, and unsatisfactory shielding, anti-aging and mechanical properties.
The cable sheath material was prepared by ultrasonic mixing and three-stage heating granulation process using plastic recycling materials combined with surfactants of dodecyl ammonium chloride, PVP K30 and coconut oleic acid diethanolamide.
It significantly improves the shielding performance, anti-aging performance and mechanical properties of cable sheath material, realizes the reuse of waste resources, is simple in process, and is suitable for industrial production.
Smart Images

Figure BDA0005178045930000081 
Figure BDA0005178045930000091
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electric wires and cables, and specifically relates to a method for preparing cable sheath material from recycled plastics and application thereof. Background Art
[0002] The insulating materials used in wires and cables are commonly known as cable materials, which mainly include plastics, rubber, nylon and other manufacturing components. Among them, plastics have good insulation, mechanical and physical properties and thermochemical stability, and their processing technology is relatively simple, with high production efficiency and abundant resources. Therefore, whether as an insulating material or a sheath material, it is the best choice for the application of wires and cables in production. The main plastics used for cables in daily life are polyvinyl chloride (PVC), polyethylene (PE), cross-linked polyethylene (XLPE) and polypropylene (PP). However, under the influence of factors such as wind, rain, sunlight (ultraviolet rays), heat and ozone, cable materials are prone to breakage of macromolecular chains and harmful changes in chemical structure, premature aging, brittleness, cracking and other phenomena, which deteriorate their physical and mechanical properties and even lose their insulation and protective functions.
[0003] Chinese invention patent publication number CN117487287A discloses an anti-aging photovoltaic cable material and a preparation method thereof, which comprises, by weight: 100 parts of PVC resin, 12-18 parts of ethylene-octene copolymer, 5-7 parts of plasticizer, 0.25-0.35 parts of modified anti-aging agent, 4-5 parts of heat stabilizer, 10-15 parts of flame retardant, 0.3-0.4 parts of coupling agent and 2-3 parts of lubricant; the modified anti-aging agent is prepared by esterification reaction of 2,2',4,4'-tetrahydroxybenzophenone and methacrylic chloride to prepare monomer 1, by ring-opening reaction of glycidyl methacrylate and tetramethylpiperidinamine, and then by substitution of n-octyl chloride and secondary amine structure in the structure to prepare monomer 2, and then the two are randomly added with 1,3-propanedithiol to form an oligomer, which has excellent long-term stable anti-aging performance.
[0004] Another Chinese invention patent publication number CN116478488A discloses an anti-aging photovoltaic cable and its preparation method, which includes, by weight: 100 parts of PVC resin, 10-20 parts of linear low-density polyethylene, 10-20 parts of ethylene-octene copolymer, 2-5 parts of masterbatch, 5.5-9 parts of composite anti-aging agent, 3-4 parts of calcium zinc stabilizer, 4-7 parts of calcium carbonate, 2-3 parts of stearic acid, 5-8 parts of epoxy soybean oil and 1.2-1.6 parts of flame retardant; the composite anti-aging agent uses a porous material composite carrier containing zinc titanium oxide and a silane coupling agent as a bridging material to graft a compound b containing an ortho-hydroxybenzophenone structure onto the surface of the composite carrier, exerting the dual functions of ultraviolet shielding + conversion in the PVC matrix, and at the same time fixing the compound b to achieve a long-term anti-ultraviolet aging effect.
[0005] Another Chinese invention patent publication number CN109161120A discloses an anti-aging material, a preparation method and an application in the preparation of a cable protection tube, comprising the following raw materials in parts by weight: 60-70 parts of PVC resin, 55-70 parts of PP resin, 30-35 parts of PE resin, 5-10 parts of an anti-aging aid, 4-6 parts of a compatibilizer, 3-5 parts of a coupling agent and 3-6 parts of an impact resister; the anti-aging aid is a mixture of an antioxidant, a light stabilizer, an ultraviolet absorber and a light shielding agent in parts by weight of 4-6:3-7:3-5:2-4, having excellent anti-aging properties, and having good flame retardancy, impact resistance and mechanical properties.
[0006] However, the preparation method of the above invention patent has many ingredients and complicated process, and the prepared cable material is still not ideal in terms of shielding performance, anti-aging performance and mechanical properties.
[0007] Therefore, there is an urgent need in the art to establish a cable sheath material that utilizes recycled plastics to prepare a cable sheath material with better shielding performance, anti-aging performance and mechanical properties. Summary of the invention
[0008] In view of the problems existing in the prior art, the present invention provides a method for preparing cable sheath material from recycled plastic material and application thereof.
[0009] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0010] A method for preparing cable sheath material from recycled plastic material, comprising the following steps:
[0011] (1) firstly mix the lubricant, antioxidant and surfactant to obtain a premix;
[0012] (2) The plastic recycling material, tackifying resin, compatibilizer and premix are mixed and granulated to obtain the cable sheath material.
[0013] Wherein, the surfactant in step (1) includes dodecyl ammonium chloride, PVP K30 and coconut oil diethanolamide.
[0014] Preferably, the surfactant comprises a mixture of dodecyl ammonium chloride, PVP K30 and coconut oil diethanolamide in a mass ratio of 3-6:1-3:2-4.
[0015] More preferably, the surfactant comprises a mixture of dodecyl ammonium chloride, PVP K30 and coconut oil diethanolamide in a mass ratio of 3-5:1.5-2.5:2-3.
[0016] Further preferably, the surfactant comprises a mixture of dodecyl ammonium chloride, PVP K30 and coconut oil diethanolamide in a mass ratio of 2:1:1.
[0017] Preferably, the surfactant needs to be soluble in ethanol, and the mass volume ratio of the surfactant to ethanol is 1g:2-3mL.
[0018] More preferably, the mass volume ratio of the surfactant to ethanol is 1 g:2 mL.
[0019] Preferably, the mixing requires ultrasound, the ultrasound temperature is 50-70°C, the ultrasound time is 0.5-1.5h, and the ultrasound power is 100-200W.
[0020] More preferably, the ultrasonic temperature is 60°C, the ultrasonic time is 1 hour, and the ultrasonic power is 200W.
[0021] Preferably, the lubricant in step (1) is selected from one or more of Clariant wax powder PE520, Honeywell 6A wax, butyl stearate, zinc stearate, calcium stearate and magnesium stearate.
[0022] More preferably, the lubricant is selected from one or more of Honeywell 6A wax, zinc stearate and magnesium stearate.
[0023] Further preferably, the lubricant is Honeywell 6A wax or zinc stearate.
[0024] Preferably, the antioxidant in step (1) is selected from one or more of antioxidant 1010, antioxidant 168 and antioxidant DLTP.
[0025] More preferably, the antioxidant is antioxidant 1010, antioxidant 168 or antioxidant DLTP.
[0026] Preferably, the plastic recycling material in step (2) includes one or more of flower bud recycling material, drip irrigation tape recycling material and bottle cap recycling material.
[0027] Preferably, the tackifying resin in step (2) comprises chloroacetic acid resin and RX-80 resin in a mass ratio of 1:1-3.
[0028] More preferably, the tackifying resin comprises chloroacetic acid resin and RX-80 resin in a mass ratio of 1:2.
[0029] Preferably, the compatibilizer in step (2) is selected from one or both of maleic anhydride grafted SEBS and maleic anhydride grafted PE.
[0030] Preferably, the mixing in step (2) requires stirring, the stirring speed is 200-500 rpm, the stirring temperature is 90-110° C., and the stirring time is 1-2 h.
[0031] More preferably, the stirring speed is 300-400 rpm, the stirring temperature is 100-110° C., and the stirring time is 1.5-2 h.
[0032] More preferably, the stirring speed is 300 rpm, the stirring temperature is 100° C., and the stirring time is 2 h.
[0033] Preferably, the granulation comprises three heating processes, the first heating temperature is 140-150°C, the second heating temperature is 160-170°C, and the third heating temperature is 170-180°C.
[0034] More preferably, the first stage heating temperature is 145°C, the second stage heating temperature is 165°C, and the third stage heating temperature is 175°C.
[0035] Preferably, the mass ratio of the lubricant, antioxidant, surfactant, plastic recycling material, tackifying resin and compatibilizer is 1-3:0.5-1.5:3-6:70-90:2-5:3-10.
[0036] More preferably, the mass ratio of the lubricant, antioxidant, surfactant, plastic recycling material, tackifying resin and compatibilizer is 2-2.5:1-1.5:4-5:80-90:3-4:5-8.
[0037] Further preferably, the mass ratio of the lubricant, antioxidant, surfactant, plastic recycling material, tackifying resin and compatibilizer is 2:1:5:90:3:6.
[0038] The invention also provides a cable sheath material prepared by the method.
[0039] The invention also provides application of the method in preparing cable wire materials.
[0040] Compared with the prior art, the present invention has the following beneficial effects:
[0041] (1) The present invention provides a method for preparing a cable sheath material using recycled plastic material, and improves the physical properties of the cable sheath material by utilizing the synergistic effect of dodecyl ammonium chloride, PVP K30 and coconut oil diethanolamide.
[0042] (2) The present invention selects a combination of chloroacetic acid resin and RX-80 resin as a tackifying resin. Compared with using a single resin, the prepared cable sheath material has excellent shielding performance, anti-aging performance and mechanical properties.
[0043] (3) The present invention utilizes recycled plastic materials to prepare cable sheath materials, thereby realizing the recycling of waste resources. The process is simple, the operation is convenient, and it is suitable for industrial production, and has a high value for promotion and application. DETAILED DESCRIPTION
[0044] It is worth noting that the raw materials used in the present invention are all common commercially available products, among which maleic anhydride grafted SEBS and maleic anhydride grafted PE are purchased from Dongguan Shenghao Plastic Raw Materials Co., Ltd.; chloroacetic acid resin, model CP-710, is purchased from Shanghai Kaiyin Chemical Co., Ltd.; RX-80 resin is purchased from Huaxiang Chemical Trading Co., Ltd.
[0045] Example 1
[0046] A method for preparing cable sheath material from recycled plastic material, comprising the following steps:
[0047] (1) First, 5 kg of surfactant was weighed and dissolved in 10 L of anhydrous ethanol, wherein the surfactant was a mixture of dodecyl ammonium chloride, PVP K30 and coconut oil diethanolamide in a mass ratio of 2:1:1. 2 kg of zinc stearate, 1 kg of antioxidant 1010 and 5 kg of surfactant were placed in an ultrasonic machine, and ultrasonicated at 60° C. and 200 W power for 1 h to obtain a premix, which was set aside.
[0048] (2) Add 30kg of recycled flower ether, 20kg of recycled drip irrigation tape, 40kg of recycled bottle cap, 3kg of tackifying resin (the tackifying resin is a mixture of chloroacetic acid resin and RX-80 resin in a mass ratio of 1:2) and 6kg of maleic anhydride grafted SEBS to the premix, and stir at 100°C and 300 rpm for 2 hours. After stirring, granulate in a twin-screw extruder at a speed of 100 rpm. The twin-screw extruder is heated in three stages, with the first stage heating temperature at 145°C, the second stage heating temperature at 165°C, and the third stage heating temperature at 175°C. Extrusion granulation is performed to obtain the cable sheath material.
[0049] Example 2
[0050] A method for preparing cable sheath material from recycled plastic material, comprising the following steps:
[0051] (1) First, 4 kg of surfactant was weighed and dissolved in 10 L of anhydrous ethanol, wherein the surfactant was a mixture of dodecyl ammonium chloride, PVP K30 and coconut oil diethanolamide in a mass ratio of 5:1.5:3. 2.5 kg of Honeywell 6A wax, 1 kg of antioxidant 168 and 4 kg of surfactant were placed in an ultrasonic machine and ultrasonicated at 60°C and 200 W for 1 h to obtain a premix for later use.
[0052] (2) Add 40kg of recycled flower ether, 15kg of recycled drip irrigation tape, 25kg of recycled bottle cap, 4kg of tackifying resin (the tackifying resin is a mixture of chloroacetic acid resin and RX-80 resin in a mass ratio of 1:1) and 7kg of maleic anhydride grafted SEBS to the premix, and stir at 100°C and 300 rpm for 2 hours. After stirring, granulate in a twin-screw extruder at a speed of 100 rpm. Heat in three stages in the twin-screw extruder, with the first stage heating temperature at 150°C, the second stage heating temperature at 160°C, and the third stage heating temperature at 170°C. Extrusion granulation is performed to obtain the cable sheath material.
[0053] Example 3
[0054] A method for preparing cable sheath material from recycled plastic material, comprising the following steps:
[0055] (1) First, 3 kg of surfactant was weighed and dissolved in 6 L of anhydrous ethanol, wherein the surfactant was a mixture of dodecyl ammonium chloride, PVP K30 and coconut oil diethanolamide in a mass ratio of 3:1:2. 1 kg of magnesium stearate, 0.5 kg of antioxidant DLTP and 3 kg of surfactant were placed in an ultrasonic machine, and ultrasonicated at a temperature of 50° C. and a power of 100 W for 1.5 h to obtain a premix, which was set aside.
[0056] (2) Add 30kg of recycled flower ether, 20kg of recycled drip irrigation tape, 20kg of recycled bottle cap, 2kg of tackifying resin (the tackifying resin is a mixture of chloroacetic acid resin and RX-80 resin in a mass ratio of 1:3) and 3kg of maleic anhydride grafted PE to the premix, and stir at 90°C and 200rpm for 2h. After stirring, granulate in a twin-screw extruder at a speed of 100rpm. The twin-screw extruder is heated in three stages, with the first stage heating temperature at 150°C, the second stage heating temperature at 170°C, and the third stage heating temperature at 180°C. Extrusion granulation is performed to obtain the cable sheath material.
[0057] Example 4
[0058] A method for preparing cable sheath material from recycled plastic material, comprising the following steps:
[0059] (1) First, 6 kg of surfactant was weighed and dissolved in 12 L of anhydrous ethanol, wherein the surfactant was a mixture of dodecyl ammonium chloride, PVP K30 and coconut oil diethanolamide in a mass ratio of 3:1:2. 3 kg of magnesium stearate, 1.5 kg of antioxidant DLTP and 6 kg of surfactant were placed in an ultrasonic machine, and ultrasonicated at 70° C. and 200 W power for 1.5 h to obtain a premix for later use.
[0060] (2) Add 50kg of recycled flower buds, 20kg of recycled drip irrigation tapes, 20kg of recycled bottle caps, 5kg of tackifying resin (the tackifying resin is a mixture of chloroacetic acid resin and RX-80 resin in a mass ratio of 1:2) and 10kg of maleic anhydride grafted PE to the premix, and stir at 110°C and 500rpm for 1h. After stirring, granulate the mixture in a twin-screw extruder at a speed of 100rpm. Heat the mixture in three stages in the twin-screw extruder, with the first stage heating temperature at 110°C, the second stage heating temperature at 160°C, and the third stage heating temperature at 180°C. Extrusion granulation is performed to obtain the cable sheath material.
[0061] Comparative Example 1
[0062] The same as Example 1, except that the surfactant is a mixture of PVP K30 and coconut oil diethanolamide in a mass ratio of 1:2.
[0063] A method for preparing cable sheath material from recycled plastic material, comprising the following steps:
[0064] (1) First, 5 kg of surfactant was weighed and dissolved in 10 L of anhydrous ethanol, wherein the surfactant was a mixture of PVP K30 and coconut oil diethanolamide in a mass ratio of 1:2. 2 kg of zinc stearate, 1 kg of antioxidant 1010 and 5 kg of surfactant were placed in an ultrasonic machine, and ultrasonicated at 60° C. and 200 W power for 1 h to obtain a premix, which was set aside.
[0065] (2) Add 30kg of recycled flower ether, 20kg of recycled drip irrigation tape, 40kg of recycled bottle cap, 3kg of tackifying resin (the tackifying resin is a mixture of chloroacetic acid resin and RX-80 resin in a mass ratio of 1:1) and 6kg of maleic anhydride grafted SEBS to the premix, and stir at 100°C and 300 rpm for 2 hours. After stirring, granulate in a twin-screw extruder at a speed of 100 rpm. The twin-screw extruder is heated in three stages, with the first stage heating temperature at 145°C, the second stage heating temperature at 165°C, and the third stage heating temperature at 175°C. Extrusion granulation is performed to obtain the cable sheath material.
[0066] Comparative Example 2
[0067] The same as Example 1, the only difference is that the surfactant is dodecyl ammonium chloride.
[0068] A method for preparing cable sheath material from recycled plastic material, comprising the following steps:
[0069] (1) First, weigh 5 kg of surfactant and dissolve it in 10 L of anhydrous ethanol, wherein the surfactant is dodecyl ammonium chloride. Place 2 kg of zinc stearate, 1 kg of antioxidant 1010 and 5 kg of surfactant in an ultrasonic machine, and ultrasonicate at 60°C and 200 W for 1 hour to obtain a premix, which is set aside.
[0070] (2) Add 30kg of recycled flower ether, 20kg of recycled drip irrigation tape, 40kg of recycled bottle cap, 3kg of tackifying resin (the tackifying resin is a mixture of chloroacetic acid resin and RX-80 resin in a mass ratio of 1:1) and 6kg of maleic anhydride grafted SEBS to the premix, and stir at 100°C and 300 rpm for 2 hours. After stirring, granulate in a twin-screw extruder at a speed of 100 rpm. The twin-screw extruder is heated in three stages, with the first stage heating temperature at 145°C, the second stage heating temperature at 165°C, and the third stage heating temperature at 175°C. Extrusion granulation is performed to obtain the cable sheath material.
[0071] Comparative Example 3
[0072] The same as Example 1, the only difference is that the mixture of dodecyl ammonium chloride and coconut oil diethanolamide is in a mass ratio of 2:1.
[0073] A method for preparing cable sheath material from recycled plastic material, comprising the following steps:
[0074] (1) First, weigh 5 kg of surfactant and dissolve it in 10 L of anhydrous ethanol, wherein the surfactant is a mixture of dodecyl ammonium chloride and coconut oil diethanolamide in a mass ratio of 2:1. Place 2 kg of zinc stearate, 1 kg of antioxidant 1010 and 5 kg of surfactant in an ultrasonic machine, and ultrasonicate at 60°C and 200 W for 1 h to obtain a premix, which is set aside.
[0075] (2) Add 30kg of recycled flower ether, 20kg of recycled drip irrigation tape, 40kg of recycled bottle cap, 3kg of tackifying resin (the tackifying resin is a mixture of chloroacetic acid resin and RX-80 resin in a mass ratio of 1:1) and 6kg of maleic anhydride grafted SEBS to the premix, and stir at 100°C and 300 rpm for 2 hours. After stirring, granulate in a twin-screw extruder at a speed of 100 rpm. The twin-screw extruder is heated in three stages, with the first stage heating temperature at 145°C, the second stage heating temperature at 165°C, and the third stage heating temperature at 175°C. Extrusion granulation is performed to obtain the cable sheath material.
[0076] Comparative Example 4
[0077] The same as Example 1, the only difference is the mixture of dodecyl ammonium chloride and PVP K30 in a mass ratio of 2:1.
[0078] A method for preparing cable sheath material from recycled plastic material, comprising the following steps:
[0079] (1) First, 5 kg of surfactant was weighed and dissolved in 10 L of anhydrous ethanol, wherein the surfactant was a mixture of dodecyl ammonium chloride and PVP K30 in a mass ratio of 2:1. 2 kg of zinc stearate, 1 kg of antioxidant 1010 and 5 kg of surfactant were placed in an ultrasonic machine and ultrasonicated at 60°C and 200 W for 1 h to obtain a premix for later use.
[0080] (2) Add 30kg of recycled flower ether, 20kg of recycled drip irrigation tape, 40kg of recycled bottle cap, 3kg of tackifying resin (the tackifying resin is a mixture of chloroacetic acid resin and RX-80 resin in a mass ratio of 1:1) and 6kg of maleic anhydride grafted SEBS to the premix, and stir at 100°C and 300 rpm for 2 hours. After stirring, granulate in a twin-screw extruder at a speed of 100 rpm. The twin-screw extruder is heated in three stages, with the first stage heating temperature at 145°C, the second stage heating temperature at 165°C, and the third stage heating temperature at 175°C. Extrusion granulation is performed to obtain the cable sheath material.
[0081] Comparative Example 5
[0082] The same as Example 1, the only difference is that the tackifying resin is chloroacetic acid resin.
[0083] A method for preparing cable sheath material from recycled plastic material, comprising the following steps:
[0084] (1) First, 5 kg of surfactant was weighed and dissolved in 10 L of anhydrous ethanol, wherein the surfactant was a mixture of dodecyl ammonium chloride, PVP K30 and coconut oil diethanolamide in a mass ratio of 2:1:1. 2 kg of zinc stearate, 1 kg of antioxidant 1010 and 5 kg of surfactant were placed in an ultrasonic machine, and ultrasonicated at 60° C. and 200 W power for 1 h to obtain a premix, which was set aside.
[0085] (2) Add 30 kg of recycled flower ether, 20 kg of recycled drip irrigation tape, 40 kg of recycled bottle cap, 3 kg of chloroacetic acid resin and 6 kg of maleic anhydride grafted SEBS to the premix, and stir at 100°C and 300 rpm for 2 h. After stirring, granulate the mixture in a twin-screw extruder at a speed of 100 rpm. Heat the mixture in three stages in the twin-screw extruder, with the first stage heating temperature at 145°C, the second stage heating temperature at 165°C, and the third stage heating temperature at 175°C. Extrusion granulation is performed to obtain the cable sheath material.
[0086] Comparative Example 6
[0087] The same as Example 1, the only difference is that the tackifying resin is RX-80 resin.
[0088] A method for preparing cable sheath material from recycled plastic material, comprising the following steps:
[0089] (1) First, 5 kg of surfactant was weighed and dissolved in 10 L of anhydrous ethanol, wherein the surfactant was a mixture of dodecyl ammonium chloride, PVP K30 and coconut oil diethanolamide in a mass ratio of 2:1:1. 2 kg of zinc stearate, 1 kg of antioxidant 1010 and 5 kg of surfactant were placed in an ultrasonic machine, and ultrasonicated at 60° C. and 200 W power for 1 h to obtain a premix, which was set aside.
[0090] (2) Add 30kg of recycled flower buds, 20kg of recycled drip irrigation tapes, 40kg of recycled bottle caps, 3kg of RX-80 resin and 6kg of maleic anhydride grafted SEBS to the premix, and stir at 100°C and 300 rpm for 2 hours. After stirring, granulate the mixture in a twin-screw extruder at a speed of 100 rpm. Heat the mixture in three stages in the twin-screw extruder, with the first stage heating temperature at 145°C, the second stage heating temperature at 165°C, and the third stage heating temperature at 175°C. Extrusion granulation is performed to obtain the cable sheath material.
[0091] Comparative Example 7
[0092] The same as Example 1, the only difference is that step (1) does not involve ultrasound.
[0093] A method for preparing cable sheath material from recycled plastic material, comprising the following steps:
[0094] (1) First, 5 kg of surfactant was weighed and dissolved in 10 L of anhydrous ethanol, wherein the surfactant was a mixture of dodecyl ammonium chloride, PVP K30 and coconut oil diethanolamide in a mass ratio of 2:1:1. 2 kg of zinc stearate, 1 kg of antioxidant 1010 and 5 kg of surfactant were placed in a blender and stirred at 60° C. and 300 rpm for 1 h to obtain a premix for later use.
[0095] (2) Add 30kg of recycled flower ether, 20kg of recycled drip irrigation tape, 40kg of recycled bottle cap, 3kg of tackifying resin (the tackifying resin is a mixture of chloroacetic acid resin and RX-80 resin in a mass ratio of 1:2) and 6kg of maleic anhydride grafted SEBS to the premix, and stir at 100°C and 300 rpm for 2 hours. After stirring, granulate in a twin-screw extruder at a speed of 100 rpm. The twin-screw extruder is heated in three stages, with the first stage heating temperature at 145°C, the second stage heating temperature at 165°C, and the third stage heating temperature at 175°C. Extrusion granulation is performed to obtain the cable sheath material.
[0096] Test Case
[0097] The cable sheath materials prepared in Examples 1-4 and Comparative Examples 1-7 were respectively tested for melt mass flow rate (i.e., melt index), density, tensile strength, low-temperature elongation at break (-18°C, 1h) and air oven thermal aging (i.e., tensile strain at break, 100°C, 240h) with reference to GB / T 15065-2009 "Black polyethylene plastic for wires and cables"; the electromagnetic shielding effectiveness low-frequency band (9kHz-20MHz) test was carried out with reference to GB / T12190-2021 "Measurement method for shielding effectiveness of electromagnetic shielding rooms", with 10 samples in each group, and the arithmetic mean of the test results was taken. The results are shown in Table 1.
[0098] Table 1 Performance test results of cable sheath materials prepared in Examples 1-4 and Comparative Examples 1-7
[0099]
[0100]
[0101] It can be seen from Table 1 that the cable sheath materials prepared in Examples 1-4 are superior to the cable sheath materials prepared in Comparative Examples 1-7 in terms of melt index, density, tensile strength, low-temperature elongation at break, tensile strain at break and electromagnetic shielding effectiveness, indicating that the cable sheath materials prepared in the present invention have excellent shielding performance, anti-aging performance and mechanical properties.
[0102] Example 1 and Comparative Examples 1-4 show that by selecting dodecyl ammonium chloride, PVP K30 and coconut oil diethanolamide as surfactants, the synergistic effect of the three is utilized to significantly improve the shielding performance, anti-aging performance and mechanical properties of the cable sheath material. Comparative Examples 5-6 show that due to the use of a single resin, the physical properties of the prepared cable sheath material are reduced to varying degrees. Example 1 and Comparative Example 7 show that in the process of preparing the premix, ultrasound is used to fully combine the raw materials, which can comprehensively improve the physical properties of the cable sheath material.
[0103] In summary, the present invention utilizes plastic recycled materials to prepare cable sheath materials, thereby realizing the recycling of waste resources, having a simple process, convenient operation, being suitable for industrial production, and having a high value for promotion and application.
[0104] Finally, it should be noted that the above content is only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Simple modifications or equivalent substitutions of the technical solution of the present invention by ordinary technicians in this field do not deviate from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing cable sheath material from recycled plastics, characterized in that: The steps include: (1) firstly mix the lubricant, antioxidant and surfactant to obtain a premix; (2) The plastic recycling material, tackifying resin, compatibilizer and premix are mixed and granulated to obtain the cable sheath material. Wherein, the surfactant includes dodecyl ammonium chloride, PVP K30 and coconut oil diethanolamide.
2. The method according to claim 1, characterized in that The surfactant comprises a mixture of dodecyl ammonium chloride, PVP K30 and coconut oil diethanolamide in a mass ratio of 3-6:1-3:2-4.
3. The method according to claim 1, characterized in that In step (1), the lubricant is selected from one or more of Clariant wax powder PE520, Honeywell 6A wax, butyl stearate, zinc stearate, calcium stearate and magnesium stearate, and the antioxidant is selected from one or more of antioxidant 1010, antioxidant 168 and antioxidant DLTP.
4. The method according to claim 1, characterized in that The surfactant in step (1) needs to be dissolved in ethanol, and the mass volume ratio of the surfactant to ethanol is 1g:2-3mL.
5. The method according to claim 1, characterized in that The mixing in step (1) requires ultrasonication, the ultrasonication temperature is 50-70°C, the ultrasonication time is 0.5-1.5h, and the ultrasonication power is 100-200W.
6. The method according to claim 5, characterized in that The plastic recycling material in step (2) includes one or more of flower bud recycling material, drip irrigation tape recycling material and bottle cap recycling material, and the compatibilizer is selected from one or both of maleic anhydride grafted SEBS and maleic anhydride grafted PE.
7. The method according to claim 1, characterized in that The tackifying resin in step (2) comprises chloroacetic acid resin and RX-80 resin in a mass ratio of 1:1-3.
8. The method according to claim 1, characterized in that The mixing in step (2) requires stirring, the stirring speed is 200-500 rpm, the stirring temperature is 90-110° C., and the stirring time is 1-2 h. The granulation includes three heating processes, the first heating temperature is 140-150° C., the second heating temperature is 160-170° C., and the third heating temperature is 170-180° C.
9. The method according to any one of claims 1 to 8, characterized in that: The mass ratio of the lubricant, antioxidant, surfactant, plastic recycling material, tackifying resin and compatibilizer is 1-3:0.5-1.5:3-6:70-90:2-5:3-10.
10. Use of the method according to any one of claims 1 to 9 in preparing cable wire materials.
Citation Information
Patent Citations
Anti-aging material, preparation method thereof and application thereof to preparation of cable protection pipes
CN109161120A
Anti-aging photovoltaic cable and preparation method thereof
CN116478488A
Anti-aging photovoltaic cable material and preparation method thereof
CN117487287A
High-temperature-resistant antibacterial cable
CN105733266A
Recycling method of waste polyvinyl chloride cable material
CN113201192A